2021
DOI: 10.1021/acssuschemeng.0c07406
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Insights into the Production of Long Chain Aliphatic Aldehydes Using a Copper-Radical Alcohol Oxidase as Biocatalyst

Abstract: The oxidation of alcohols is a cornerstone reaction in chemistry, notably in the flavors and fragrances industry where long chain aliphatic aldehydes are major odorant compounds. In a context where greener alternatives are sought after, biocatalysis holds many promises. Here, we investigated the ability of the alcohol oxidase from Colletotrichum graminicola (CgrAlcOx) -an organic cofactor-free enzyme belonging to the copper-radical oxidases (CROs) class -to convert industrially-relevant long chain aliphatic al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 73 publications
9
61
0
Order By: Relevance
“…Carboxylic acid was not noticeable for hexan-1-ol but was observed after 16 hours of conversion of octan-1-ol only when HRP was present in the reaction. Indeed, this overoxidation to the acid was shown previously to be mediated by HRP in the case of fatty aldehydes > C6 (21). In the same study, we observed that in the case of benzaldehyde derivatives (i.e.…”
Section: Biocatalytic Production Of Odorant Aldehydes Using Cdealcoxsupporting
confidence: 81%
See 4 more Smart Citations
“…Carboxylic acid was not noticeable for hexan-1-ol but was observed after 16 hours of conversion of octan-1-ol only when HRP was present in the reaction. Indeed, this overoxidation to the acid was shown previously to be mediated by HRP in the case of fatty aldehydes > C6 (21). In the same study, we observed that in the case of benzaldehyde derivatives (i.e.…”
Section: Biocatalytic Production Of Odorant Aldehydes Using Cdealcoxsupporting
confidence: 81%
“…Conversion results showed that CdeAlcOx behave similarly to CgrAlcOx with all the tested substrates (Figure 6). As previously observed with CgrAlcOx (21,33), CdeAlcOx alone was unable to promote full alcohol conversion. However, when both accessory enzymes were added to the reaction mixture, full conversion was readily achieved in 15 minutes.…”
Section: Biocatalytic Production Of Odorant Aldehydes Using Cdealcoxsupporting
confidence: 78%
See 3 more Smart Citations